Transcriptional Profiling of Banana Shrimp Fenneropenaeus merguiensis with Differing Levels of Viral Load. (1st June 2016) - Powell, Daniel; Knibb, Wayne; Nguyen, Nguyen Hong; Elizur, Abigail
Abstract : Viral pathogens are of serious concern to the culture of penaeid shrimps worldwide. However, little is known about the molecular response of shrimp to viral infection. Selective breeding has been suggested as an effective long-term strategy to manage viral disease, though more information on gene function is needed to help inform breeding programs. The study of cultured banana shrimp ( Fenneropenaeus merguiensis ) infected with hepatopancreatic parvo-like virus (HPV) provides a unique opportunity to explore the host response to viral infection independent of challenge testing. To gain insight into the genetic mechanisms underlying resistance to high levels of HPV, we examined hepatopancreas tissue from six full-sib groups of banana shrimp with differing levels of HPV infection for differences in gene expression. A total of 404 differentially expressed genes were identified with 180 being over-expressed and 224 under-expressed among high-HPV full-sib groups. Based on homology analysis, a large proportion of these genes were associated with processes reported to be involved in the immune response of crustaceans, including pattern recognition proteins, antimicrobial peptides, components of the prophenoloxidase system, and antiviral activity. The results indicate shrimp from high-HPV full-sib groups appear to have a lower presence of important immune response elements, yet possess upregulated putative antiviral pathways. Within the differentially expressed genes, over 4000 sequence variants were identified to be exclusive to either the high- or low-HPV full-sib groups. To our knowledge, this is the first report of differential expression analysis using RNA-Seq to explore differences in viral load among high- and low-HPV full-sib groups of cultured shrimp. This research has provided additional insight into our understanding of the mechanisms involved in the response of this shrimp species to a naturally occurring viral pathogen. Sequence variants identified in this study offer an exceptional resource for mining gene-associated markers of HPV resistance.